The Politics of Gender Equality Australian Lessons in an Uncertain World - Johnson, Carol; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This open access book provides the first in-depth study of the development of federal gender equality politics and policy in Australia from the 1970s to the present day. Australia has a history of gender equality innovation, including granting women's suffrage long before equivalent countries. From the 1970s on, it became the first country to introduce a women's adviser, femocrats (feminist bureaucrats) and gender responsive budgeting but then fell behind, partly due to the influence of Anglosphere neoliberalism. However, the Albanese government has pledged to make Australia a world leader in gender equality again. The book situates Australia in an international context, assessing the useful, though sometimes salutary, lessons which the Australian experience provides. It engages with key literature, including feminist political theory, discursive framing analysis, gendered public policy analysis, LBGTIQ+ issues, path dependency, and gender and leadership. It will interest academics, undergraduate and postgraduate researchers, public policy experts and practitioners, and a broader readership interested in issues of gender equality. The book makes innovative contributions to the study of the politics of gender equality policy, addressing what a gender equality policy agenda could look like if the needs of women, in all their intersectional social diversity, were the driving force. In doing so, it addresses a range of issues that are impacting the future of women, including an ongoing pandemic, technology, education and training agendas, issues of sovereign capability, securitisation, climate change and the growth of campaigns that oppose so-called (3z(Bgender ideology(3y(B. It explores how current government agendas, such as the focus on wellbeing, could be made even more gender-inclusive. Finally, the book suggests that Australia, as a multicultural but predominantly Western, settler-colonial society situated in the Asia-Pacific has some potentially unique insights to offer in a world facing major geoeconomic and geopolitical change. Carol Johnson is Emerita Professor in the Department of Politics and International Relations, School of Social Sciences, University of Adelaide, Australia.s
Chapter 1. In the Frame: Women and the discursive construction of gender equality in theory and practice -- Chapter 2. Great Hopes: (3z(BSecond-wave(3y (BSeventies$1 (BFeminism and state provision from Whitlam to Fraser (1972-1983) -- Chapter 3. Labor$1 (Bs Economic rationalism: Women under the Hawke & Keating Governments (1983-1996) -- Chapter 4. Defending the mainstream: Women and neoliberalism under the Howard Government (1996-2007) -- Chapter 5. Social democracy, the "Fair Go" and Gender Wars: Women under the Rudd and Gillard Governments (2007-13) -- Chapter 6. Framing a business case for Equality: Women under the Abbott, Turnbull & Morrison Governments (2013-2022) -- Chapter 7. Unfinished business: the Albanese government and Gender equality policy (2022 -?) -- Chapter 8. Gender equality and the failure of political imagination: Lessons for reframing in uncertain times.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Identity politics; Political planning; Politics and Gender; Public Policy